2016
DOI: 10.1038/ijo.2016.193
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic dysfunction following weight cycling in male mice

Abstract: BackgroundCombatting over-weight or obesity can lead to large fluctuations in an individual’s body weight, often referred to as weight cycling or “yo-yo” dieting. Current evidence regarding the potentially damaging effects of these changes is conflicting.MethodsHere, we assess the metabolic effects of weight cycling in a murine model, comprising three dietary switches to normal or high fat diets at 6 week intervals; male C57BL/6 mice were fed either a control (C) or high fat (F) diet for 6 weeks (n=140/group).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
4
21
1
Order By: Relevance
“…36,37 Moreover, multiple clinical and animal studies, including the present study ( Figures 1G and 2D), indicated that healthy and unhealthy diet switch induced weight cycling ultimately increases body fat gain, specifically in the visceral adipose tissue. 4,38 Notably, the present study demonstrated increased A, qPCR results of Il-6 and Il-8 in primary hepatocytes stimulated with media from indicated 3T3-L1 cells. B, Representative western blots of p-STAT3 and STAT3 (left) with quantification result of p-STAT3/STAT3 ratio (right) in primary hepatocytes stimulated with media from indicated 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 53%
“…36,37 Moreover, multiple clinical and animal studies, including the present study ( Figures 1G and 2D), indicated that healthy and unhealthy diet switch induced weight cycling ultimately increases body fat gain, specifically in the visceral adipose tissue. 4,38 Notably, the present study demonstrated increased A, qPCR results of Il-6 and Il-8 in primary hepatocytes stimulated with media from indicated 3T3-L1 cells. B, Representative western blots of p-STAT3 and STAT3 (left) with quantification result of p-STAT3/STAT3 ratio (right) in primary hepatocytes stimulated with media from indicated 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 53%
“…In these studies, EE was not measured. Other studies either did not analyze BW regain after BW cycling [ 11 ], or did not allow animals to regain BW in their natural way towards a new equilibrium [ 8 , 12 , 22 , 23 ], or did not include one-BW cycle control groups [ 6 , 8 , 9 , 24 ], or used very short duration cycles and/or total food deprivation [ 15 , 16 , 25 ], or analyzed only one cycle [ 14 ]. In the three studies with which we could compare, BW gain over the total study period was reduced after BW cycling [ 17 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the only other BW cycling study performed in mice (of unknown gender), comparable food efficiencies between three cycling groups were observed [ 22 ]. Other BW cycling studies, using dietary changes to induce cycles showed no or increased food efficiency [ 5 , 7 , 14 ] or did not measure this parameter [ 6 , 8 , 10 , 11 , 22 , 26 , 27 ]. Based on these data, it seems that BW cycling without dietary changes does not lead to increased food efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.1101/554980 doi: bioRxiv preprint manifestations of weight gain in response to a WD. Interestingly, improved nutrition, dieting and weight loss do not invariably lead to a return to normal plasma metabolite concentrations, and these altered plasma levels of specific metabolites may be contributing to the increased cardiovascular disease risk observed in patients with repeated cycles of weight gain and loss (often termed yoyo dieting or weight cycling) in both females [10,11] and males [12]. However, the exact pattern of metabolic changes during this weight cycling has not been characterized, and it is unknown how quickly a WD exposure (with or without weight gain and subsequent loss) causes long-term changes.…”
Section: Introductionmentioning
confidence: 99%